A model to derive software maintenance policy decision. (1st January 2013) - Subash Babu, A.; Sanghi, Udit; Rehman, Ateekh Ur; AL-Shayea, Adel M.; Sharaf, Mohamed Abdel Fattah
The problem of software maintenance is gaining considerable importance both for the user industry and the service providers. The area of equipment maintenance is very well developed one, but the same is not true for the software maintenance. In this paper, a model is developed and solved for deriving software maintenance decision. This model uses two criteria of maximum availability and minimum maintenance cost to make a decision between corrective maintenance and preventive maintenance. The model was used to obtain the appropriate maintenance policy and also for performing sensitivity analysis, the results of which are presented in this paper. The model presented in this paper has significant potential for application and further research.